Morphometric distinction between Acute bulbosus phytoliths (silicified epidermal hair cells) from Panicum miliaceum and Setaria italica leaves - Ting An; Jiaxin Chen; Yunfei Zheng; Shude Huo; Wanfa Gu (Vegetation History and Archaeobotany, 2024)

Development of crop growing from the late Yangshao to early Longshan period in the Zhengluo region of central China: phytolith evidence from the Shuanghuaishu site - Binggui Sun; Yuzhang Yang; Wanfa Gu; Weiya Li; Qilong Cui; Xin Zhou; Juzhong Zhang (Vegetation History and Archaeobotany, 2024)

Prehistoric damaging earthquake promoted the decline of “Heluo Ancient State” in Early China - Xiu Hu; Peng Lu; Youli Li; Duowen Mo; Wanfa Gu; Qingri Liu; Ailun Guo; Panpan Chen; Hui Wang; Yan Tian; Xu Wang; Yayi Hu; et al. (Science China Earth Sciences, 2023)

The emergence of early microblade technology in the hinterland of North China: a case study based on the Xishi and Dongshi site in Henan Province - Chao Zhao; Youping Wang; Wanfa Gu; Songzhi Wang; Xiaohong Wu; Xiaoxu Gao; Youcheng Chen; Yulong Li (Archaeological and Anthropological Sciences, 2021)

Early evidence of trepanation along the Yellow River Basin in Neolithic China - Yawei Zhou; Shuang Lin; Wanfa Gu; Letian He; Qun Zhang; Hui-Yuan Yeh (Archaeological and Anthropological Sciences, 2020)
Trepanation is a long-lasting ancient practice found around the world with diverse motivations. However, the distribution and motivation of intentional trepanation in China remain unclear. This study presents one of the earliest trepanations on a male adult individual who is unearthed from the Shuanghuaishu site in Gongyi, Henan, dating back to the late Yangshao cultural period (3500–2900 BC). The macroscopic and microscopic observation, alongside with micro-CT scan, are conducted to further evaluate the conditions on the edges of the perforation and intracranial situation. The oval perforation is located on the occipital bone, and neither fracture nor apparent healing signs are observed on the margins. Archeological evidences and simulated experiment indicate that the trepanation could be conducted by drilling the tables of the skull with a V-bladed stone tool. In view of the location of the perforation and the limited details on the edges, the motivation behind the trepanation could be due to the medical treatment of trauma on the occipital bone or a postmortem ritual. The analysis of the early trepanation along the Yellow River Basin provides further evidence on the ancient human behavior and enriches our understanding of the origin and distribution of trepanation in Neolithic China.